Bridging Theory and Practice: Embedding Micro learning of Enterprise Systems in University Lectures - Wienand, Mareen; Seufert, Sarah; Schütte, Reinhard (Conference: SAP Academic Community Conference, 2024)
Due to the digitalization, there is a growing need for specialists in organizations withcompetencies in enterprise systems (ES) like SAP S/4HANA. These specialists can either be trained within the organization or recruited by hiring new employees, such as university graduates. However, for graduates to develop these competencies, they need to be trainedalready during studies. To counter this requirement, micro learnings, where learning content ispresented in short activities, could be embedded into lectures. However, there is currently a lack of guidance for embedding ES micro learning content into lectures. Towards the developmentof a micro learning framework based on a structured literature review and consortium research,we were able to identify 10 requirements for ES micro learning courses. Finally, we developed a framework that can serve as a guide for lecturers. The framework will be applied in university teaching for the first time in summer term 2024.